PERANCANGAN MEDIA PEMBELAJARAN KOMPUTER DAN JARINGAN DASAR BERBASIS AUGMENTED REALITY - Geovanne Farell; Mutawafika Rusliputri (Jurnal Teknologi Informasi dan Pendidikan, 2021)
The Covid-19 pandemic has shifted the entire teaching and learning process into online learning, including practicum subjects. However, online learning methods are less effective in practicum subjects. This condition is detrimental to vocational school students, especially the 10th-grade in TKJ majors who will learn assembly and computer maintenance practicum. The purpose of this research is to produce learning media in the form of applications on the Android platform based on Augmented Reality that can display 3D models, 3D animation, and videos about assembling computer hardware along with an explanation of its functions and maintenance. The method used in this learning media is marker-based tracking that uses marker paper to be tracked by an AR camera to bring up 3D objects. The research result is the development of AR-based learning media that can help TKJ student in